Imbalance of tyrosine by modulating TyrA arogenate dehydrogenases impacts growth and development of Arabidopsis thaliana. (18th January 2019) - de Oliveira, Marcos V. V.; Jin, Xing; Chen, Xuan; Griffith, Daniel; Batchu, Sai; Maeda, Hiroshi A.
Summary: l ‐Tyrosine is an essential aromatic amino acid required for the synthesis of proteins and a diverse array of plant natural products; however, little is known on how the levels of tyrosine are controlled in planta and linked to overall growth and development. Most plants synthesize tyrosine by TyrA arogenate dehydrogenases, which are strongly feedback‐inhibited by tyrosine and encoded by TyrA1 and TyrA2 genes in Arabidopsis thaliana . While TyrA enzymes have been extensively characterized at biochemical levels, their in planta functions remain uncertain. Here we found that TyrA1 suppression reduces seed yield due to impaired anther dehiscence, whereas TyrA2 knockout leads to slow growth with reticulate leaves. The tyra2 mutant phenotypes were exacerbated by TyrA1 suppression and rescued by the expression of TyrA2, TyrA1 or tyrosine feeding. Low‐light conditions synchronized the tyra2 and wild‐type growth, and ameliorated the tyra2 leaf reticulation. After shifting to normal light, tyra2 transiently decreased tyrosine and subsequently increased aspartate before the appearance of the leaf phenotypes. Overexpression of the deregulated TyrA enzymes led to hyper‐accumulation of tyrosine, which was also accompanied by elevated aspartate and reticulate leaves. These results revealed that TyrA1 and TyrA2 have distinct and overlapping functions in flower and leaf development, respectively, and that imbalance of tyrosine, caused by altered TyrA activity and regulation, impacts growth and development of Arabidopsis. The findings provide critical bases for improving the production of tyrosine and its derived natural products, and further elucidating the coordinated metabolic and physiological processes to maintain tyrosine levels in plants. Significance statement: l ‐Tyrosine is an essential aromatic amino acid required for synthesis of proteins and a diverse array of plant natural products. In this study, we show by in planta genetic analysis that Arabidopsis synthesizes tyrosine mainly via the arogenate intermediate through tight regulation of TyrA enzymes, and that both up‐ and down‐regulation of TyrA enzymes lead to imbalance of tyrosine and impact leaf development.